The Effect of Audiovisual Health Promotion on Knowledge, Attitudes, and Behaviors Related to the Prevention of Recurrent Chest Pain in Patients with Coronary Heart Disease - Fiddi Septiani; Budiman; Ayu Laili; Agus Riyanto (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2026)
Cardiovascular disease remains a leading cause of mortality worldwide, with a continuously increasing prevalence. In Indonesia, coronary heart disease (CHD) contributes substantially to cardiovascular-related deaths, highlighting the importance of effective secondary prevention strategies. Health promotion using appropriate educational media is essential to improve patients’ knowledge, attitudes, and self-care behaviors. This study aimed to examine the effect of audiovisual health promotion on knowledge, attitudes, and behaviors related to the prevention of recurrent chest pain among patients with coronary heart disease. A quantitative quasi-experimental study was conducted using a pretest–posttest control group design. Participants were patients diagnosed with coronary heart disease who were assigned to intervention and control groups. The intervention group received audiovisual-based health education, while the control group received standard care. Data were analyzed using univariate, bivariate, and multivariate analyses. Paired t-tests, independent t-tests, and Wilcoxon tests were used for bivariate analysis, and multiple logistic regression was applied for multivariate analysis. The results showed a significant improvement in knowledge (p = 0.001) and attitudes (p = 0.018) in the intervention group after exposure to audiovisual health promotion. However, no significant effect was observed on preventive behaviors related to recurrent chest pain (p = 0.084). In conclusion, audiovisual health promotion effectively improves knowledge and attitudes among patients with coronary heart disease but does not significantly influence preventive behaviors. These findings suggest that while audiovisual media are effective for cognitive and affective outcomes, additional or sustained interventions are required to promote behavioral change in the secondary prevention of coronary heart disease.